Personaliti dan emosi pegawai tadbir Sarawak : satu kajian kes - Dayang Ratna Kesmawati, Bt. Abang Morni. (Universiti Malaysia Sarawak (UNIMAS), 1999)
This study aims to investigate personality and emotion of Sarawak Administrative Officer (SAO). Questionnaires were used to obtain ff!edback from a total of 90 respondent. The questionnaires comprised the information about respondents' demography, personality and emotion dimension. The independent variables in this research were demographic factor which are gender and ethnic while the dependent variables were personality (Uncertainty avoidance, Masculinity femininity, Inpil'idllalism collectivism and Power distance) and i!moiion (Angry and Avoidance, Angry and Defensive. Angry and Blaming Others and AnglY and Comparisons). Ttest, Pearson Con'elation Coefficient and MIIltiple Linear Regression were used to test the questions developed in this research. The ji".~ings showed that there is no significant relationship between persflnality and gender at p>0.05 level. While emotion and gender showed that there is no Significant relat~onship b,etween this two variables. Relationship between personality a'1d eth1!i(; showed that all personality dimension ho,$ no significant relationship with ethnic with p> 0.05. Rf!lqtionship between emotion and ethnic also sh(JWeq there is no relationship qetween these twq variabl,!s. The results from Pearson's CorrelatiQn Coefficient indicated thflt UncertC!inty avoidance personality ('r'= ~0/37), Masculinity femininity ('r '= 0.322), Individualism collectivism ('r'.= 0.004) and Power distance ('r'= 0.390) has no significant relationship with emotion., Multiple Linear Regression Analysis revealed that all personality dimensiqn has no contribution towards respondents' personality. A Multiple Linear Regression Analysis on emotion revealed that emotion dimension has no contribution on S.A.O behaviour. In conciusion. the study important to infonn the leader how perso nality and emotion can injluencesthe'm: The jindi~;gs ofthis study also prO\;ide support for the literature which ~an be helpful to future researcher